THE ORIGIN OF THE POLITICAL CONSCIOUSNESS IN MUHAMMADIYAH: AN EPISTEMOLOGICAL ANALYSIS TOWARD INDONESIA’S MUSLIM-REFORMIST MOVEMENT - Al-Hamdi, Ridho (Indonesian Journal of Islamic Literature and Muslim Society, 2020)
This article examines the origin of the political consciousness of Muhammadiyah. Thus, the paper aims to investigate the origin of the political consciousness of Muhammadiyah to be a reference for Muhammadiyah’s elites, functionaries, cadres, and members in the way of thinking and behaving, mainly in the context of political affairs. Methodologically, this article is qualitative research by applying two techniques in data-gathering: documentary and interview. The finding demonstrates that the origin of political consciousness of Muhammadiyah can be traced back into a fourfold thing: the influence of the Islamic reformist idea mainly coming from the middle east, the awareness of liberation from backwardness, the awareness of liberation from colonization, and the awareness of liberation from the Christian penetration.